2021
DOI: 10.1128/cmr.00188-20
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Oxazolidinone Resistance Genes in Gram-Positive and Gram-Negative Bacteria

Abstract: Seven mobile oxazolidinone resistance genes, including cfr , cfr (B), cfr (C), cfr (D), cfr (E), optrA , and poxtA , have been identified to date. The cfr genes code for 23S rRNA methylases, which confer a multiresistance phenotype that includes resistance to phenicols, lincosamides, oxazolidinones, pleuromutilins, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 321 publications
0
97
0
7
Order By: Relevance
“… CfrWT used for the starting point for directed evolution is displayed as the top sequence (Cfr) in blue. Cfr(B), Cfr(C), Cfr(D), and Cfr(E) are Cfr homologs that have been functionally characterized, reviewed here ( Schwarz et al, 2021 ). Remaining sequences are Cfr homologs that clade with Cfr or Cfr-like genes as described previously ( Stojković et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… CfrWT used for the starting point for directed evolution is displayed as the top sequence (Cfr) in blue. Cfr(B), Cfr(C), Cfr(D), and Cfr(E) are Cfr homologs that have been functionally characterized, reviewed here ( Schwarz et al, 2021 ). Remaining sequences are Cfr homologs that clade with Cfr or Cfr-like genes as described previously ( Stojković et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, mutations obtained through directed evolution have been observed in Cfr homologs that share less than 80% sequence identity with Cfr. Methionine (M) at position 26 is observed for the functionally characterized Cfr homologs Cfr(B) ( Deshpande et al, 2015 ; Marín et al, 2015 ; Hansen and Vester, 2015 ) and Cfr(D) ( Pang et al, 2020 ), which have been recovered from human-derived isolates and share 74% and 64% amino acid identity with Cfr, respectively ( Schwarz et al, 2021 ; Figure 4—figure supplement 5 ). We also observe lysine (K) at position 2, methionine (M) at position 26, and glycine (G) at position 39, akin to N2K, I26M, and S39G mutations, for a number of Cfr homologs that clade with functional Cfr or Cfr-like genes ( Stojković et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, all of the poxtA genes described in enterococci have been plasmid-borne, suggesting that plasmids play an important role in the dissemination of the poxtA gene among enterococci ( 22 , 23 ). In this study, two mobilizable poxtA -carrying plasmids were identified in E. faecalis and E. lactis , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…P variant was distributed in Clostridium difficile and Campylobacter jejuni and EYDNDM variants were found in Enterococcus faecalis, Staphylococcus aureus, Staphylococcus sciuri , Enterococcus avium. 12 Given that the relationship between optrA variants and linezolid MIC remains unclear, novel optrA variants in E. faecium is of concern.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] It is mostly reported in Enterococcus but also detected in Staphylococcus sciuri, Streptococcus suis, and other Gram-positive or Gram-negative strains. 12 OptrA is often located on chromosomes or plasmids and can be transmitted by mobile genetic elements such as transposons and insertion sequences. [13][14][15] The most recently reported poxtA gene, mediating resistance to oxazolidinones, tetracyclines, and phenicols, was first described in an MRSA isolate from respiratory secretion of an Italian patient.…”
Section: Introductionmentioning
confidence: 99%